STUDENTS’ PERCEPTIONS OF ETHICAL AI USE IN EFL ACADEMIC WRITING - Bakhromova Iroda Takhirovna (International Journal of Literature and Language Studies, 2026)
The rapid development of artificial intelligence (AI) technologies has significantly influenced the field of education, particularly English as a Foreign Language (EFL) academic writing. AI-powered tools such as grammar checkers, paraphrasing systems, and generative AI platforms have transformed the way students plan, draft, revise, and edit academic texts. Despite the pedagogical benefits of these technologies, concerns regarding academic integrity, plagiarism, authorship, and ethical use remain highly debated in higher education. This article examines students’ perceptions of ethical AI use in EFL academic writing through the analysis of recent scholarly literature, institutional reports, and international educational policies. The study explores how EFL learners perceive the advantages and limitations of AI-assisted writing tools and identifies the ethical challenges associated with their use in academic contexts. Findings indicate that students generally perceive AI as a supportive educational tool that enhances language accuracy, vocabulary development, and writing confidence. However, many students also express uncertainty regarding the boundaries between acceptable assistance and academic dishonesty. The article further discusses the importance of digital literacy, institutional guidelines, and ethical awareness in promoting responsible AI use in academic writing. The study concludes that universities and educators should establish clear frameworks for ethical AI integration in EFL instruction to balance technological innovation with academic integrity.